Analisis Tingkat Literasi Nasabah Bank Syariah Pada Kontrak Murabahah - Asmaul Husna; Marliyah Marliyah; Haris Al Amin; Julfan Saputra; Wahyu Syarvina (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2021)
The purpose of this research is to examine the level of understanding of Islamic bank customers who have entered into murabahah contracts, as well as the factors that influence customer decisions to use Islamic banks for murabahah financing. 45 Islamic bank customers who have taken murabaha financing were selected as samples. The data used is primary data collected from customers who have taken murabaha credit through surveys and direct interviews. Qualitative analytical approach was used in data analysis. The findings show that customers are not aware of the murabahah financing arrangements.